Empirical Study About Behavioral Intention to use Internet Banking Service - Thi Van, Nguyen (International Journal of Psychosocial Rehabilitation, 2020)
This paper aimed to identify the factors that influenced the behavioral intention to use internet banking service. Survey data were collected from 344customers living inHo Chi Minh City, Vietnam. The research model was proposed from the studies of behavioral intention to use internet banking service. The reliability and validity of the scale were evaluated by Cronbach's Alpha, Average Variance Extracted (Pvc), and Composite Reliability (Pc). The model selection of AIC showed that the behavioral intention to use internet banking service was impacted by six components of the behavioral intention to use internet banking service such as Performance Expectancy, Effort Expectancy, Facilitating Conditions, Social Influence, Safety/Security, and Convenience.